The effect of cocoa pod husk as organic fertilizer on the growth of tea (Camellia sinensis (L) o. Kuntze) under varying light intensities in Ibadan – South West Nigeria (2019)
Tea is one of the components of human diets due to its antioxidative properties and nutritive values. Light intensity and soil fertility are the major abiotic factors affecting the growth of tea (Camellia sinensis(L) O. Kuntze). Tea performs well under low light intensity and fertile soil. In Nigeria, tea production is predominant in Mambilla Plateau due to cool weather. To meet the increasing demand for tea, there is need for soil fertility improvement and expansion of the growing area of tea to the lowland ecology of Nigeria. A pot experiment was conducted in Cocoa Research Institute of Nigeria (CRIN), Idi-Ayunre, Ibadan, South-West Nigeria to assess the effect of varying light intensities and soil amendment with Cocoa Pod Husk (CPH) and NPK fertilizer on the growth and dry matter production of tea cuttings. Milled CPH fertilizer was applied at the rate, 75kgN ha-1 (13.39g pot-1), 150kgN ha-1 (26.79g pot-1) and 300kgN ha-1 (53.57g pot-1), and NPK 5:1:1 (150kgN ha-1) fertilizer while zero fertilizer served as control. The tea plants were grown under four different light intensities of 25, 45, 65 and 100% by using varying densities of palm fronds to cover the top and sides of the sheds. The results showed that CPH at 300kgN ha-1, 45% and 65% light intensities enhanced vegetative growth and dry matter accumulation in the tea plants. The 65% light increased the number of leaves, leaf area, number of branches, plant height, stem diameter and total dry matter by 188%, 400%, 14%, 30%, 21% and 620% respectively compared to the 100% light. The 45% light increased the number of leaves, leaf area, plant height, stem diameter and total dry matter by 155%, 369%, 21%, 16% and 656% respectively compared to the 100% light. CPH at 300kgN ha-1 increased number of leaves, leaf area, number of branches, plant height, stem diameter and total dry matter by 69%, 155%, 62%, 28%, 24% and 75% respectively compared to the control. When compared to the NPK fertilizer, CPH at 300kgN ha-1 increased number of leaves, leaf area, number of branches, plant height and total dry matter by 25%, 32%, 12%, 1% and 47% respectively. On interaction, tea cuttings grown under 45 and 65% light intensities and received CPH at 300kgN ha-1 produced significantly (P=0.05) higher number of leaves, leaf area, number of branches, root dry weight, stem dry weight, leaf dry weight and total dry matter; while 65% light interaction with NPK fertilizer enhanced significantly (P=0.05) higher plant height and stem diameter.